2019
DOI: 10.1111/jfpp.14166
|View full text |Cite
|
Sign up to set email alerts
|

Influence of irradiation and moringa leaf powder on the amino acid and fatty acid profiles of chicken meat stored under various packaging materials

Abstract: This study was carried out to observe the changes causes by irradiation doses (0, 1.5, and 3 kGy) on oxidation stability, amino acids, and fatty acids in chicken meat incorporated with or without moringa leaf powder (MLP) during refrigerator storage of 14 days under aerobic and vacuum packaging. The results revealed that Thiobarbituric acid reactive substances (2.10 ± 0.02 MDA/kg) and Peroxide value (1.13 ± 0.01 meq peroxide/kg) were higher in aerobic as compared to vacuum in treatment with 3 kGy + 2% MLP. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
3
10
1
Order By: Relevance
“…Furthermore, Kim et al () also proposed the fact that unsaturated fatty acid contents decreased in the treated samples using 4 kGy radiation compared to that of the control, which is similar to our observation. The results are further supported by the findings of Nisar, Arshad, Yasin, Arshad, and Nadeem () who found that fatty acid contents were slightly decreased by the irradiation treated chicken meat. The results are in accordance with the estimations done by Jo, An, Arshad, and Kwon () who depicted that fatty acid contents were also decreased in with the use of e‐beam irradiation in the smoked meat of duck.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, Kim et al () also proposed the fact that unsaturated fatty acid contents decreased in the treated samples using 4 kGy radiation compared to that of the control, which is similar to our observation. The results are further supported by the findings of Nisar, Arshad, Yasin, Arshad, and Nadeem () who found that fatty acid contents were slightly decreased by the irradiation treated chicken meat. The results are in accordance with the estimations done by Jo, An, Arshad, and Kwon () who depicted that fatty acid contents were also decreased in with the use of e‐beam irradiation in the smoked meat of duck.…”
Section: Resultssupporting
confidence: 85%
“…Effect of e-beam irradiation on fatty acid content (mg/g) of frozen duck meat of Nisar, Arshad, Yasin, Arshad, and Nadeem (2019) who found that fatty acid contents were slightly decreased by the irradiation treated chicken meat. The results are in accordance with the estimations done by Jo, An, Arshad, and Kwon (2018) who depicted that fatty acid contents were also decreased in with the use of e-beam irradiation in the smoked meat of duck.…”
Section: Ta B L Ementioning
confidence: 99%
“…formulated a study on the manipulation of alpha-lipoic acid and wheat germ oil in broiler diet and found to have lower TBARS value in the nuggets during storage. Nisar, Arshad, Yasin, Arshad, and Nadeem (2019) found the same trend of slowing down the formation of TBARS in chicken meat by incorporation of moringa leaf powder.…”
Section: Thiobarbituric Acid Reactive Substances (Tbars)mentioning
confidence: 58%
“…It plays a significant role as a natural antioxidant and shelf life enhancer (Al‐Juhaimi, Ghafoor, Hawashin, Alsawmahi, & Babiker, 2016). The combination of gamma irradiation and moringa leaf powder (MLP) has synergistic effect on the safety of meat products (Nisar, Arshad, Yasin, Arshad, & Nadeem, 2019).…”
Section: Introductionmentioning
confidence: 99%